2016
DOI: 10.1080/23299460.2016.1216709
|View full text |Cite
|
Sign up to set email alerts
|

Responsible innovation for decent nonliberal peoples: a dilemma?

Abstract: It is hard to disagree with the idea of responsible innovation (henceforth, RI), as it enables policymakers, scientists, technology developers, and the public to better understand and respond to the social, ethical, and policy challenges raised by new and emerging technologies. RI has gained prominence in policy agenda in Europe and the United States over the last few years. And, along with its rising importance in policy-making, there is also a burgeoning research literature on the topic. Given the historical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 43 publications
0
35
0
Order By: Relevance
“…Another limitation is the fact that the concept of responsible innovation emerged from a predominantly European discourse, and is consequently based on liberal democratic values (Wong 2016). Which is why, among other reasons, the research lens of responsible research and innovation cannot be used one-on-one with innovation in the global south (Macnaghten et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Another limitation is the fact that the concept of responsible innovation emerged from a predominantly European discourse, and is consequently based on liberal democratic values (Wong 2016). Which is why, among other reasons, the research lens of responsible research and innovation cannot be used one-on-one with innovation in the global south (Macnaghten et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, of the thirteen countries in which STIR studies have so far been carried out, only Hungary (and possibly China) can be considered to be developing. And while there are increasing instances of studies pertaining to RRI more general being carried out in developing countries (e.g., de Hoop et al, 2016), RRI itself is arguably based on democratic and liberal values (such as freedom, participation and equality), and on "Western ethics" (Wong 2016 Wong 2016) showed that when integrating RRI in different -nonliberalcultures, ethics, religion, values, culture, or innovation environment of the country concerned should be taken into account. Wong (2016) details this dilemma and emphasizes: since research and innovation have global nature owing to international cooperation, the understanding of 'responsibility' may differ causing conflicts.…”
Section: Introductionmentioning
confidence: 99%
“…39 See, e.g. Wong (2015Wong ( , 2016 on how current debates on the ethics of geo-engineering omit concerns that are important from a non-Western perspective. 40 See e.g.…”
Section: Are There Universal Norms?mentioning
confidence: 99%